Industrial sectors and local competitive strengths in Rio de Janeiro (2011)
This article is the result of an investigation made in Rio de Janeiro, Brazil.The purpose of this article is first, to identify a degree of specialization of theindustry, and second, to identify the strongest and most competitive industries inthe region. The aim of this interested investigation made in Rio de Janeiro wasto determine the degree in which competitive conditions lead to industrial growthwithin the different areas of its productive specialization and to collaborationamong each other. Results were obtained through a simple correspondence analysisof a questionnaire used in 302 enterprises, all of them in Rio de Janeiro.